Long-Term Winter Population Trends of Corvids in Relation to Urbanization and Climate at Northern Latitudes - Jokimäki Jukka; Kaisanlahti-Jokimäki Marja-Liisa; Suhonen Jukka (MDPI, 2022)
Simple Summary
Corvids (e.g., crows, magpies and jays) are an important part of urban settlements, especially during winter. To understand the factors affecting the long-term population trends of corvids, we counted wintering corvids in 31 human settlements along a 920 km latitudinal gradient in Finland during four winters between 1991 and 2020. We detected a total of five corvid species, from which the Hooded Crow, the Eurasian Magpie and the Eurasian Jackdaw were found to be common. During the study period, the number of Eurasian Jackdaws increased, and their distribution range moved northwards. No corresponding changes were observed for the Hooded Crow or the Eurasian Magpie. Neither the local-level urban-, climate- nor food-related factors correlated with the changes in the numbers and growth rates of the corvids. No interspecific interactions were observed. We assume that the Eurasian Jackdaw has benefitted from the decreased persecution, and probably also from the large-scale climate warming. Our results suggest that urban settlements are quite stable wintering environments for generalist and omnivorous corvids.
Abstract
Corvids (crows, magpies, jays) live in a close association with humans, and therefore knowledge about their population status and changes will be an essential part of monitoring the quality of urban environments. Wintering bird populations can track habitat and climate changes more rapidly than breeding populations. We conducted a long-term (1991-2020) winter census of corvid species in 31 human settlements along a 920 km latitudinal gradient in Finland. We observed a total of five corvid species: the Eurasian Magpie (occurring in 114 surveys out of 122; total abundance 990 ind.), the Hooded Crow (in 96 surveys; 666 ind.), the Eurasian Jackdaw (in 51 surveys; 808 ind.), the Eurasian Jay (in 5 surveys; 6 ind.) and the Rook (in 1 survey; 1 ind.). Only the numbers of the Eurasian Jackdaw differed between the study winters, being greater at the end of the study period (2019/2020) than during the earlier winters (1991/1992 and 1999/2000). The average growth rate (lambda) of the Eurasian Jackdaw increased during the study period, whereas no changes were observed in the cases of the Hooded Crow or the Eurasian Magpie. The growth rate of the Eurasian Jackdaw was greater than that observed in the Finnish bird-monitoring work, probably because our data came only from the core area of each human settlement. Even though the number of buildings and their cover increased in the study plots, and the winter temperature differed between winters, the average growth rate (lambda) of corvid species did not significantly correlate with these variables. These results suggest that urban settlements are stable wintering environments for the generalist corvids. The between-species interactions were all positive, but non-significant. Despite the total number of winter-feeding sites being greater during the winter of 1991/1992 than during the winter of 2019/2020, the changes in the numbers of feeding stations did not correlate with the growth rates of any corvid species. We assume that the Eurasian Jackdaw has benefitted from the decreased persecution, and probably also from large-scale climate warming that our study design was unable to take in to account. Our results indicated that wintering corvid populations succeed well in the human settlements in Finland. We recommend conducting long-term corvid research, also during breeding season, to understand more detailed causes of the population changes of corvids along an urban gradient.Without year-round long-term monitoring data, the conservation and management recommendations related to the corvid species in urban habitats may be misleading.